2011
DOI: 10.1016/j.juro.2011.03.113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postoperative C-Reactive Protein Level on Recurrence and Prognosis in Patients With N0M0 Clear Cell Renal Cell Carcinoma

Abstract: Nonnormalization of postoperative C-reactive protein is a strong predictor of recurrence and prognosis. Patients with C-reactive protein 0.3 mg/dl or greater at recurrence might not survive as long as those with C-reactive protein less than 0.3 mg/dl at recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…This is consistent with recent publications in cancer cohorts using the same threshold measurement. [15][16][17] The results of the current study are also in agreement with those of previous reports 18 that indicated, in patients with non-small cell lung cancer, although an increased risk of mortality occurs with a C-reactive protein measurement above approximately 4 mg/L, the risk increase is steeper between 8 mg/L and 16 mg/L. Indeed, some authors have adopted other thresholds for C-reactive protein, such as > 5 mg/L, into the GPS.…”
Section: Optimization Of the Gps/proctor Et Almentioning
confidence: 99%
“…This is consistent with recent publications in cancer cohorts using the same threshold measurement. [15][16][17] The results of the current study are also in agreement with those of previous reports 18 that indicated, in patients with non-small cell lung cancer, although an increased risk of mortality occurs with a C-reactive protein measurement above approximately 4 mg/L, the risk increase is steeper between 8 mg/L and 16 mg/L. Indeed, some authors have adopted other thresholds for C-reactive protein, such as > 5 mg/L, into the GPS.…”
Section: Optimization Of the Gps/proctor Et Almentioning
confidence: 99%
“…A decrease in CRP level (to <0.5 mg/dl) during treatment predicts better prognosis in patients with metastatic RCC, and a prolonged period of normal CRP level is associated with prolonged survival (15). Ito et al (16) reported that non-normalization of postoperative CRP (≥0.3 mg/dl) strongly predicted recurrence and prognosis in 263 patients with N0M0 RCC who underwent nephrectomy. Shinohara et al (17) reported that response rate and 1-year progression-free survival were significantly higher in patients with normalized CRP compared with those in non-normalized patients treated with IFN-α combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tatokoro et al (14) reported that CRP decreased to normal after cytoreductive nephrectomy in 74% of patients who had elevated CRP prior to surgery, and Ito et al (16) reported that 65.8% of patients achieved CRP normalization following nephrectomy. By contrast, Saito et al (15) reported that, among patients who underwent immunotherapy, metastasectomy, or both, only 49% achieved CRP normalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential tissue biomarkers that were tested failed to predict RCC recurrence in our cohort. Although, serum CRP levels have been shown to be predictive for RCC outcomes in several studies [29,30], few studies have evaluated tissue expression of CRP [11]. In addition, HIF1α, HIF2α, and CAIX have shown variable ability to predict recurrence or survival in several studies [3,10,21,27].…”
Section: Discussionmentioning
confidence: 99%